Romania : Fifth Review Under the Stand-By Arrangement: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2012)
Growth in Romania is likely to moderate in 2012, weighed down by the euro area slowdown. The Fifth Review Under the Stand-By Arrangement highlights that Romania's overall track record under the program continues to be strong. All performance criteria for the fifth program review were met, except for accumulation of central government arrears, which was missed by a small margin. The indicative target on local government arrears accumulation was also missed. Progress was made on the large and difficult structural agenda, although more action is needed.